2020
DOI: 10.3390/jmse8090676
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variability of Ice Algal Trophic Markers—With Recommendations about Their Application

Abstract: Assessing the relative importance of sea ice algal-based production is often vital for studies about climate change impacts on Arctic marine ecosystems. Several types of lipid biomarkers and stable isotope ratios are widely used for tracing sea ic-associated (sympagic) vs. pelagic particulate organic matter (POM) in marine food webs. However, there has been limited understanding about the plasticity of these compounds in space and time, which constrains the robustness of some of those approaches. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 61 publications
(102 reference statements)
3
23
0
Order By: Relevance
“…This finding is in agreement with an earlier study from the Nansen Basin when both firstyear and multi-year ice were studied (Kohlbach et al 2016: δ 13 C FA iPOM: −28.4 to −23.4 ‰; δ 13 C FA pPOM: −39.3 to −26.4 ‰) and with a study of seasonal firstyear ice in the Bering Sea (Wang et al 2014: δ 13 C FA iPOM: −26.5 to −21.0 ‰; δ 13 C FA pPOM: −30.4 to −27.0 ‰). Leu et al (2020) found an increasing trend in δ 13 C FA values in a seasonally sea-ice-covered fjord in Svalbard throughout spring (April−May), suggesting that bloom succession and an increase in underice light play a role in these values, similar to seasonal changes determined by bulk δ 13 C values. To date, studies investigating δ 13 C FA values of individual fatty acids in POM throughout the Arctic are not as ubiquitous compared to studies of bulk δ 13 C POM.…”
Section: δ 13 C Differences In Biomarker Fatty Acids Between Habitatssupporting
confidence: 61%
See 1 more Smart Citation
“…This finding is in agreement with an earlier study from the Nansen Basin when both firstyear and multi-year ice were studied (Kohlbach et al 2016: δ 13 C FA iPOM: −28.4 to −23.4 ‰; δ 13 C FA pPOM: −39.3 to −26.4 ‰) and with a study of seasonal firstyear ice in the Bering Sea (Wang et al 2014: δ 13 C FA iPOM: −26.5 to −21.0 ‰; δ 13 C FA pPOM: −30.4 to −27.0 ‰). Leu et al (2020) found an increasing trend in δ 13 C FA values in a seasonally sea-ice-covered fjord in Svalbard throughout spring (April−May), suggesting that bloom succession and an increase in underice light play a role in these values, similar to seasonal changes determined by bulk δ 13 C values. To date, studies investigating δ 13 C FA values of individual fatty acids in POM throughout the Arctic are not as ubiquitous compared to studies of bulk δ 13 C POM.…”
Section: δ 13 C Differences In Biomarker Fatty Acids Between Habitatssupporting
confidence: 61%
“…To date, studies investigating δ 13 C FA values of individual fatty acids in POM throughout the Arctic are not as ubiquitous compared to studies of bulk δ 13 C POM. Isotopic enrichment in bulk δ 13 C values in iPOM over pPOM is seasonally and regionally variable, depending on environmental and physiological factors in addition to taxonomic community composition and biomass, which can be minimal or absent at times (de la Vega et al 2019, Leu et al 2020.…”
Section: δ 13 C Differences In Biomarker Fatty Acids Between Habitatsmentioning
confidence: 99%
“…In contrast, sterols yield less specific dietary information, but can be used to distinguish, to some extent, phytoplankton-produced versus animal-produced carbon (Drazen et al, 2008;Ruess and Müller-Navarra, 2019). Each of these biochemical methods has strengths and weaknesses, but when applied in combination they yield different facets to feeding and are a powerful approach to study food webs (Leu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A similar seasonal change from pelagic to sympagic carbon source composition could be expected for Arctic crustaceans, provided they feed to some extent throughout the winter and can actually access the ice-associated carbon. Preferred dietary sources of marine animals and their seasonality can be elucidated from the composition of lipidbased trophic markers (Leu et al, 2020). Their stability when transferred along the marine food chain makes them valuable trophic proxies in disentangling food-web relationships and revealing the importance of varying carbon sources (e.g., Scott et al, 1999;Iverson, 2009).…”
Section: Introductionmentioning
confidence: 99%